A Magnetically Capsule Robot for Biomedical Application - Qiang Fu; Xi Zhang; Songyuan Zhang; Chunliu Fan; Zhuocong Cai; Lili Wang (Applied Bionics and Biomechanics)
Magnetic-driven capsule robot has been widely studied due to its advantages of safety and reliability. However, when doctors carry out clinical examination, the capsule robot cannot achieve the ideal control effect due to the influence of the external magnetic field air gap. This paper is based on the kinetic energy theorem, combined with the principle of spiral mechanism in mechanical design foundation to construct a calculation method of energy utilization and to improve the control effect of capsule robot, suitable for the human gastrointestinal tract precise control of capsule robot to perform a variety of complex tasks. By calculating the energy utilization rate of the capsule robot under the control of external magnetic field, the method can improve the energy utilization rate by improving the equation parameters, so that the capsule robot can run according to the doctor’s ideal performance in practical application. Based on the analysis of the magnetic driven screw capsule robot, the model of the utilization rate of the external magnetic field of the capsule robot is established, and the fluid simulation of the capsule robot is carried out by using the method of computational fluid dynamics. The simulation results and experimental results show that the control effect of capsule robot can be improved by calculating the energy utilization rate of the robot, which is of great significance to human clinical examination and treatment.